2017
DOI: 10.1111/pbr.12537
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of molecular markers for improving the phosphorus efficiency in crop plants

Abstract: Phosphorus (P) is the second most growth limiting macronutrient after nitrogen and plays several important roles in all organisms including plants. In soil, P is available in both organic and inorganic forms. P deficiency reduces the growth and yield of several crop plants. Plants respond to P deficiency by the phenotypic changes especially by the modification of root architecture. Molecular marker-assisted breeding (MAB) has been proposed as an important tool to identify and develop improved varieties of crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 142 publications
(177 reference statements)
0
41
0
1
Order By: Relevance
“…Phosphorus is key component of nucleic acids and plant hormones and determines the yield and quality of a crop [13,14]. Phosphorus deficiency in soil can be overcome by phosphorus fertilizer application, excess application leads to delayed formation of reproductive organs [15]. Uptake of phosphorus from soil is complex as the phosphorus is bound to calcium in alkaline soils and iron and aluminium in acid soils [16].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is key component of nucleic acids and plant hormones and determines the yield and quality of a crop [13,14]. Phosphorus deficiency in soil can be overcome by phosphorus fertilizer application, excess application leads to delayed formation of reproductive organs [15]. Uptake of phosphorus from soil is complex as the phosphorus is bound to calcium in alkaline soils and iron and aluminium in acid soils [16].…”
Section: Introductionmentioning
confidence: 99%
“…In most agricultural croplands, elemental phosphorus is considered to be the second most limiting plant nutrient after nitrogen [31]. The results indicated that topsoil P was greater than subsoil P which is often associated with added P sorption, greater biological activities, and accumulation of organic materials.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Phosphorus is a macro element required for biological growth and development, in particular it is essential for the synthesis of important biochemical substances such as DNA, RNA and ATP in all living organisms [1,2] . In its natural state in soil, P exists in the form of organic phosphorus (P o ) and inorganic phosphorus (P i ), with the former accounting for 50% to 80% of soil P [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…2can be directly used by plants, accounting for less than 0.01% of available P in the soil and even less than 0.001% in the low-P fields. As a result, P use efficiency (PUE) in the soil ranges from 20% to 30%, limiting crop yields by 30%-40% [1,[7][8][9][10][11][12] . Meanwhile, temperature, moisture, pH and other soil factors also affect the P concentration and form.…”
Section: Introductionmentioning
confidence: 99%